Luciogobius punctilineatus n. sp., a new earthworm goby from southern Japan - Koreeda, Reo; Motomura, Hiroyuki (Zootaxa, 2022)
Luciogobius punctilineatus n. sp. is described on the basis of 21 type specimens from Kyushu, and the Koshiki and Osumi Islands, southern Japan. It is also found in Kochi Prefecture (Shikoku) and Amami-oshima island (Ryukyu Islands), Japan, confirmed by examination of non-type specimens. The genus Luciogobius includes 15 valid and several undescribed species, and most of them inhabit interstitial spaces of stones and gravel in the intertidal zone. The new species is characterized by the following combination of characters: total second dorsal-fin rays 10–12 (modally 11); total anal-fin rays 12–14 (13); pectoral-fin rays 8–12 (10); vertebrae 16–18 + 22–24 = 39–42 (17 + 23 = 40); pectoral-fin posterior margin slightly concave; pelvic fins united, forming a ventral disc; snout relatively short, length 3.1–4.3% of SL; anus to anal-fin origin (AAA) distance twice body depth at anus, 11.4–16.9% of SL; snout length less than 34.7% of AAA distance; pre-anus length less than 85.5% of pre-anal-fin length; single poorly defined black longitudinal line along mid-lateral body region from behind pectoral fin to caudal-fin base, indistinct anteriorly (line embedded, visible through semi-transparent muscle tissue in fresh or live specimens); black spots forming a single longitudinal row on mid-lateral body surface from behind pectoral fin to caudal-fin base (more distinct in preserved specimens).